Die Musikalien des Hamburger Organisten Valentin Pralle († 1565) - Huck, Oliver (Die Musikforschung, 2023)
Even though the manuscript Ms. Hans. III,4 of the Staats- und Universitätsbibliothek Hamburg has been missing since World War II, its descriptions by Johann Ludwig von Bouck and Hugo Leichsenring contribute valuable information about the music library of Valentin Pralle, organist at the Swedish court in 1542 and at St. Katharinen in Hamburg from 1542 until his death in 1565. The article identifies the intabulation sent in a letter by the organist Johan Kellner to Pralle in 1554 (one of the earliest manuscripts in “new” German organ tablature) as the five-part motet Respice in me et miserere mei deus by G. Domale, based either on the prints RISM 15511 or 155412. Furthermore, the antigraph of four Latin motets and ten French chansons, copied in partbooks by Pralle himself, can be identified as the Selectissimae necnon familiarissimae cantiones (RISM 15407). There was another set of partbooks with four hitherto unknown German songs for four and five voices of which at least the first (cited in a quodlibet by Melchior Franck first printed in RISM F 1651) is by Johann Stahel, of whom so far only one five-part secular song in the fifth volume of Georg Forster’s Frischen teutschen Liedlein has been known. The article furthermore discusses a fascicle with German and French songs with incipits of texts only, for which neither Bouk nor Leichsenring give any information concerning the notation. From a note by Otto Kade in his copy of Ludwig Senfl’s Wohl kumbt der Mai taken from RISM 153417, it is evident that Ms. Hans. III,4 contained monophonic versions of this and other songs of which some or at least their melodies are hitherto unknown.